FOREIGN EXPERIENCE OF STOCK MARKET DEVELOPMENT, AND POSSIBILITIES FOR USING IT IN DEVELOPING THE UZBEKISTAN STOCK MARKET - Nishanova Nargiza Burkhonidinovna (PEDAGOGS, 2025)
Abstract: World experience shows that the most important indicators associated with the level of economic development of countries and high per capita national income, including (a large number of types of securities traded on the stock market and high liquidity, high dividend policy in joint-stock companies (JSCs), and improved stock exchange trading systems), are explained by the high level of development of the stock market, in particular, the high share of capitalization of the stock market (SMP) in relation to the volume of gross domestic product (GDP).